Depression, stress and anxiety among Khartoum University students who stay in war-afflicted regions in Sudan 2024 - Hajar Saad Salih; Shahd Ahmed Ibrahim; Mawahib Ahmed A. Gaded; Leena Abdo Abdurahman Osman; Maab FadlAllah Mahmoud; Mohamed H. Elbadawi; Group of collaborators (BMC Psychiatry)
Abstract Background The ongoing conflict in Sudan leads to widespread displacement and increased mortality, significantly impacting the mental health of populations in conflict zones. This study aims to fill the gap and assess the level of stress, depression, and anxiety among Khartoum University undergraduate students in war-afflicted regions. Methods A cross-sectional study among 443 undergraduate students Was conducted using cluster and stratified sampling techniques. Data was collected using a valid questionnaire in a period of one month and analyzed using SPSS and a regression model to assess factors affecting distress. Results The study shows high levels of psychological distress, particularly among female students. Median anxiety and stress levels were 12.50 and 14.00, respectively, for women, significantly higher than those for men (p < 0.001). Faculty, physical health, time management, and support systems were also significantly correlated with distress levels. Students in the Faculty of Forests and Animal Breeding exhibited the highest levels of depression and anxiety. Poor physical health and seeking professional help were strongly associated with increased psychological distress. Regression analysis identified gender (p = 0.001) and time management (p = 0.022) as significant predictors of overall distress. Conclusion Undergraduate university students in war regions experience high levels of stress, anxiety, and depression due to conflict situations. These findings reflect the urgent need for interventions such as community-based programs and counselling. We recommended future studies to explore long-term impacts on students' mental health.